La nic 41 (agricultura) y su repercusión en la valoración de los activos biológicos de la compañía agrícola Katcosi S.A del cantón Ventanas, periodo 2012 - Tamayo Avilés, Liliana María (2015)
This research was conducted at the Agricultural Company KATCOSI SA Windows Canton , in the period of 2012 , which allowed to prescribe the accounting treatment and the subsequent presentation and disclosure in the financial statements for agriculture , for which the contribution of the financial staff and the owner of the collateral company presentation of financial information on the biological assets has analyzed the difference that determines the application of the International Accounting Standard IAS 41 in the financial statements was checked and it was determined the change that the application of the Standard International Accounting Standards (IAS ) 41 in structuring the financial statements. To achieve the expected results of the investigation, several research methods including exploratory , descriptive , and correlational techniques such as observation, document review, interview with the owner of the company, surveys of the 10 people involved were used to either way with the handling of the financial information of the company. With the information collected, we proceeded to analyze and interpret it, discovering that much of the financial staff of the company know about the applicability of IFRS and specifically of IAS 41 relating to IAS 41. Additionally, the demonstration of the hypothesis was performed using the statistical model Chi - Square, discovered that the accepted hypothesis is : "The study of accounting with its revelation of the International Accounting Standard ( IAS ) 41 SI allow the SA Agricultural Company KATCOSI proper preparation of Financial Statements" . Among the most important recommendations, it is contemplated to conduct and implement a training plan for staff financial and administrative area KATCOSI Agricultural Company SA , related processes , regulations, adoption of IFRS and IAS 41 specifically to so that financial officers , can generate financial information as established by the Superintendency of Companies of Ecuador.